Effect of Si-doped InGaN underlayers on photoluminescence efficiency and recombination dynamics in InGaN/GaN quantum wells - Church, S A; Christian, G M; Barrett, R M; Hammersley, S; Kappers, M J; Frentrup, M; Oliver, R A; Binks, D J (IOP Publishing, 2021)
Abstract: A series of single InGaN/GaN quantum wells (QWs) with a Si-doped InGaN underlayer were studied to investigate the impact of the underlayer on photoluminescence efficiency and recombination dynamics. The thickness of the GaN capping layer was varied between samples, which changed the electric field across the QW due to band bending near the surface. When directly exciting the wells, thermionic emission of carriers results in a rapid drop in the photoluminesence efficiency with increasing temperature such that no emission is observed above 100 K. However, exciting above the energy of the barriers caused the intensity of the QW emission to drop more slowly, with up to 12% of the 10 K emission intensity remaining at 300 K. This difference is attributed to hole transfer from the underlayer into the QW, which increases in efficiency at higher temperatures, and is enhanced by stronger electric fields present in the GaN barriers of samples with thinner GaN capping layers. Further, the sample with the narrowest cap layer of 2 nm has a different shape and characteristic time for its photoluminescence decay transient and a different emission energy temperature dependence than the other samples. This behaviour was ascribed to a change in carrier localisation for this sample due to a reversal of the net field across the well compared to the other samples.
Keywords: Paper; Semiconductors and photonics; Si; doped; InGaN; underlayers; photoluminescences; quantum well